2019
DOI: 10.1002/adfm.201904545
|View full text |Cite
|
Sign up to set email alerts
|

Donor–Acceptor‐Conjugated Polymer for High‐Performance Organic Field‐Effect Transistors: A Progress Report

Abstract: Polymeric semiconductors have demonstrated great potential in the mass production of low-cost, lightweight, flexible, and stretchable electronic devices, making them very attractive for commercial applications. Over the past three decades, remarkable progress has been made in donor-acceptor (D-A) polymer-based field-effect transistors, with their charge-carrier mobility exceeding 10 cm 2 V −1 s −1 . Numerous molecular designs of D-A polymers have emerged and evolved along with progress in understanding the cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
336
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(345 citation statements)
references
References 136 publications
(201 reference statements)
8
336
1
Order By: Relevance
“…Organic field‐effect transistors (OFETs) have the advantages of low‐cost, large‐area, or mass‐production processing, and are used for a variety of potential applications. [ 1–4 ] Therefore, many efforts have been made to improve their electrical performance over the past decades. Impressively, some recent studies have shown that the field‐effect mobility ( µ FET ) has been increased to more than 10 cm 2 V −1 s −1 by synthesizing structurally optimized organic semiconducting materials or by applying appropriate processing techniques (chemical doping, aligned crystal structure, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Organic field‐effect transistors (OFETs) have the advantages of low‐cost, large‐area, or mass‐production processing, and are used for a variety of potential applications. [ 1–4 ] Therefore, many efforts have been made to improve their electrical performance over the past decades. Impressively, some recent studies have shown that the field‐effect mobility ( µ FET ) has been increased to more than 10 cm 2 V −1 s −1 by synthesizing structurally optimized organic semiconducting materials or by applying appropriate processing techniques (chemical doping, aligned crystal structure, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…In recent, donor–acceptor (D–A) conjugated copolymers (CCPs) have been widely investigated on the band gap engineering in the industrial and academic areas for flexible organic field-effect transistors, photocatalysts, polymer solar cells, and electrochromic applications [ 1 , 2 , 3 , 4 ]. Among of D–A CCPs, the copolymer of aniline with thiophene is known to increase the conductivity of polyaniline (PANI) and thiophene-based polymeric materials have great electrochromic properties suitable for displays such as high contrast, fast switching times, and stabilities [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…10 Therefore, extensive efforts have continuously been made to improve the device performance, particularly for OFETs and solar cells (OPVs & PSCs). [11][12][13][14] Among all these efforts, it is apparent that development of organic semiconductors (OSCs), which provide the core functionality of the devices, have played a significant role in advancing this field.…”
Section: Introductionmentioning
confidence: 99%